The Uses and Limits of Small-Scale Military Interventions - Watts, Stephen (RAND Corporation, 2012)
The authors assess the utility and limitations of "minimalist stabilization"-small-scale interventions designed to stabilize a partner government engaged in violent conflict-and propose policy recommendations concerning when minimalist stabilization missions may be appropriate and the strategies most likely to make such interventions successful, as well as the implications for U.S. Army force structure debates and partnership strategies.